Prescription Pathways from Initial Medication Use to Triple Therapy in Older COPD Patients: A Real-World Population Study. Issue 1 (31st December 2022) - Jiang, Lili; Kendzerska, Tetyana; Aaron, Shawn D.; Stukel, Therese A.; Stanbrook, Matthew B.; Tan, Wan; Pequeno, Priscila; Gershon, Andrea S.
Abstract: Background and objective: Triple therapy with an inhaled corticosteroid (ICS), a long-acting β2 -agonist bronchodilator (LABA) and a long-acting muscarinic antagonist (LAMA) is recommended as step-up therapy for chronic obstructive pulmonary disease (COPD) patients who continue to have persistent symptoms and increased risk of exacerbation despite treatment with dual therapy. We sought to evaluate different treatment pathways through which COPD patients were escalated to triple therapy. Methods: We used population health databases from Ontario, Canada to identify individuals aged 66 or older with COPD who started triple therapy between 2014 and 2017. Median time from diagnosis to triple therapy was estimated using the Kaplan-Meier method. We classified treatment pathways based on treatments received prior to triple therapy and evaluated whether pathways differed by exacerbation history, blood eosinophil counts or time period. Results: Among 4108 COPD patients initiating triple therapy, only 41.2% had a COPD exacerbation in the year prior. The three most common pathways were triple therapy as initial treatment (32.5%), LAMA to triple therapy (29.8%), and ICS + LABA to triple therapy (15.4%). Median time from diagnosis to triple therapy was 362 days (95% confidence interval:331–393 days) overall, but 14 days (95% CI 12–17 days) in the triple therapy as initial treatment pathway. This pathway was least likely to contain patients with frequent or severe exacerbations (22.0% vs. 31.5%, p  < 0.001) or with blood eosinophil counts ≥300 cells/µL (18.9% vs. 22.0%, p  < 0.001). Conclusion: Real-world prescription of triple therapy often does not follow COPD guidelines in terms of disease severity and prior treatments attempted.